The Relationship between Body Mass Index (BMI) and Hypertension Incidence at Royal Prima Hospital in 2024 - Dix Munthe Dix Munthe; Taufik Delfian (International Journal of Health and Pharmaceutical (IJHP), 2025)
Background: Hypertension affects 1.4 billion adults globally and remains inadequately controlled. Body mass index (BMI) accounts for 65 to 75 percent of primary hypertension cases, yet hospital-based evidence from Southeast Asian populations remains limited. Objective: This study determined the relationship between BMI and hypertension incidence at Royal Prima Hospital Medan in 2024. Methods: This cross-sectional analytical study employed total population sampling including 69 respondents meeting inclusion criteria. Data were extracted from medical records and analyzed using univariate analysis and Spearman rank correlation test. Results: Among respondents, 84.1 percent experienced hypertension, with 52.2 percent possessing a BMI greater than 25 kg/m². All respondents with BMI greater than 25 kg/m² exhibited hypertension compared to 66.6 percent of those with normal BMI (p=0.000). Conclusion: A statistically significant relationship exists between elevated BMI and hypertension incidence, confirming obesity as a critical modifiable risk factor for hypertension development in hospital settings. Weight management through lifestyle modification represents an essential intervention strategy for hypertension prevention and control.